PENGARUH USAHA PENGOLAHAN SAGU SKALA KECIL TERHADAP BAKU MUTU AIR ANAK SUNGAI - Bambang Haryanto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
The objective of this research is to study the influence of small-scale sago processing industry to standard quality of Ciheuleut river water in Cibuluh Sub-district, District of Bogor Utara, and City of Bogor. The method used is to analyse the water in laboratory and subsequently the result is compared to standard quality of tapioca industry. Response of community in the area regarding this sago processing industry is gathered by performing interview in the form of questionnaire (number of community response is 35). Water samples used for water analysis are from 4 locations. They are water beforeflowing into the processing unit (A), water after filtration (B), process disposal water collected 1 m apart from filter (C) and discarded water that flows into river (D). Water analysis applied utilizes chemical analysis that includes pH, COD, BOD, DO, turbidity, cyanide and TSS (Total Soluble Solid) parameters. Laboratory analysis shows that location B has turbidity level that exceeds the standard quality required. Result of hypothesis test shows that hypothesis zero (H0) acceptable and alternative hypothesis rejected. It means water disposal waste of sago processing industry does not alter thequality of water disposal. Community feel disturbed (46%) on the existence of sago processing industry. The disturbance consists of liquid waste (20%), unpleasant odour due to solid waste (51.1%), and noise (22.9%). Unpleasant odour due to solid waste occurs during rainny season. 60% of responses say that water disposal of sago processing industry leads to river turbidity; whereas 40% thinks that it does not make any difference.River turbidity brings about itchiness (28.6%) while 68.6% says it does not make any difference. 71.4% of responses show that the existence of sago processing industry is beneficial to the community.